ANOSMIA AND AGEUSIA IN PATIENTS WITH COVID-19 - Abbas, Tahir Ghulam; Siddiqui, Atif Hafeez; Zaidi, Syed Hasan Abbas; Rahim, Danish -Ur-; Shaikh, Irfan Ahmed; Soomro, Arfat Bashir; Farrukh, Muhammad Shuja; Kamal, Jahanzeb (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the prevalence and diagnostic significance of anosmia and ageusia among COVID-19 positive patients of Karachi, Pakistan.Study Design: Cross-sectional study.Place and Duration of Study: Dr Ruth K. M. Pfau Civil Hospital, (Dow University of Health Sciences), Karachi Pakistan, from Jan 2021 to Feb 2021.Methodology: The data were collected prospectively from 265 COVID-19 positive patients. Some patients were interviewed over the telephone, while for patient's ease, an online Google form was also formed, facilitating the online data collection. The patient's demographics, comorbidities, allergies, and COVID-19 associated characteristics were inquired. The statistical analysis was performed on SPSS version 23.Results: The observed frequency of anosmia and ageusia in COVID-19 patients was 49.1% & 43.8% respectively. The median time to recovery was 8-8.5 days (median) for both symptoms. We found no significant difference for gender, BMI, marital status, residential area, comorbidities and reason for long-standing breathing difficulties between patients with or without both anosmia and ageusia (p>0.05). Furthermore, most of the cigarette smokers reported none of the two symptoms (anosmia and ageusia), 24% and 25.2% of COVID-19 positive cases with smoking history were presented without anosmia and ageusia, respectively (p